Numerical study of uneven wall-heating effect for a one side rib-roughened cooling channel subject to rotation - Wang, Z.; Corral, R. (Aeronautical journal, 2018)
This paper investigates the impact of the wall-heating conditions on the heat transfer performance of a rotating channel with one side smooth and one side roughened by 45° inclined ribs. Previous experimental and numerical studies for single-ribbed wall-heated channels showed that rotation has a significant negative impact on heat transfer performance. In order to investigate this uncommon behaviour, RANS simulations were conducted under three different wall-heating conditions in the present study: ribbed wall heated, all walls heated and adiabatic conditions. Numerical results show that the presence of uneven wall-heating conditions has a negligible impact on the stationary case, but it has a large influence on rotational cases, in both, the heat transfer and the flow field. The underlying reason is that in rotating cases, uneven heating results in different buoyancy effects on the trailing and leading walls of the channel that alter the main flow velocity profile. As a consequence, also secondary flows and heat transfer performance are affected.